Determinants of customer loyalty: a review and future directions - Abu-Alhaija, Ahmad Saifalddin; Raja Yusof, Raja Nerina; Hashim, Haslinda; Jaharuddin, Nor Siah (AENSI Publications, 2018)
This paper aims to provide a summary review on the existing loyalty models. It focuses on the key factors and perspectives that can assist marketing scholars and professionals in enhancing customer’s loyalty. A review of the literature has been employed to provide further understandings on customer’s loyalty and its research priorities. The findings of this paper contends that integrating cultural and religious influences into existing models would enhance customer’s loyalty. The study also argues that there are three groups of loyalty antecedents should be taken into consideration. They are 1) loyalty’s primary determinants (PD), which include, customer’s satisfaction, trust, perceived value, and perceived service quality; 2) loyalty’s secondary determinants (SD), which include, other loyalty factors based on the research nature and context; and 3) loyalty’s moral determinants (MD), which include, spiritual, cultural, and religious factors of target markets. Additional propositions and directions are also provided to create efficient loyalty models. Marketing scholars have given inadequate attention to cultural and religious influences in studying customer’s loyalty. This article is a commentary research on previous loyalty models. It is hoped that the propositions provided in the study would inspire future researchers in emerging proper and effective loyalty models.